An experimental study of sunflower husk pellets combustion - Islamova Svetlana (EDP Sciences, 2021)
The thermogravimetric study of the sunflower husk pellets combustion was carried out at three heating rates: 5, 10, and 20 °C/min to increase the efficiency of agricultural waste disposal methods. The husk combustion process can be divided into several stages: the stage of moisture evaporation and the release of light fractions of volatile substances, the main stage of the release of volatiles and combustion, as well as the stage of the carbonaceous residue after-burning. The maximum mass loss was observed in the experiment with a heating rate of 10 °C/min, and it was equal to 91.99% of the total weight of organic matter. The average residual mass for all experiments was 3%. The higher heating value (HHV) of sunflower husk pellets was 19.2 MJ/kg. When implementing a biomass boiler with a capacity of 430 kW, the return period will be 3.43 years.